Strategies for Creating Competitive Advantage: A Case Study of Kading Xay Engineering Construction in Oudomxay Province - DAOPHAKHIT, Sonesuly; Duangvilaykeo, Thipphavanh; Phengsavat, Sithivikhone (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study aims to 1) examine the competitive strategies of Kading Xay Engineering Construction and Architecture Survey-Design Sole Co., Ltd.; and 2) explore strategic approaches to further enhance the company’s competitive advantage. Through SWOT analysis based on in-depth interviews with four key company personnel, the research identifies the firm's strategic position within the growing construction sector. 1) The research findings revealed that: Key strengths include proficient project management systems and technical expertise, though challenges exist in standardizing certain operational procedures. The company operates in a favorable environment characterized by infrastructure expansion and government investment policies, while facing threats from increasing market competition and economic volatility. 2) Strategic recommendations emphasize quality enhancement, technological adoption (AI-BIM-Drone integration), service differentiation, and sustainable business expansion. The study contributes practical insights for construction firms in emerging markets seeking to establish competitive advantages.